CTLA-4 -1722T/C Polymorphism and Systemic Lupus Erythematosus Susceptibility: A Meta-analysis Involving Ten Separate Studies. (February 2013) - Zhu, Ji-Min; Li, Bai-Kun; Chen, Gui-Mei; Feng, Chen-Chen; Cen, Han; Fan, Yin-Guang; Wang, Bin; Pan, Hai-Feng; Ye, Dong-Qing
<x xml:space="preserve">Abstract</x> Cytotoxic T lymphocyte associated antigen-4 (CTLA-4) -1722T/C polymorphism has been identified as a susceptibile gene for systemic lupus erythematosus (SLE), but studies are inconsistent. To better assess the association between CTLA-4 -1722T/C polymorphism and SLE, a meta-analysis was performed, including 10 studies, total of 1 387 patients and 1 617 controls. Overall, the CTLA-4 -1722T/C polymorphism was significantly associated with SLE susceptibility (T VS C: OR = 1.17, 95% CI = 0.86–1.60, P = 0.304; T/T VS C/C: OR = 1.92, 95% CI = 1.09–3.39, P = 0.024; T/C VS C/C: OR = 1.50, 95% CI = 0.91–2.49, P = 0.114; T/T VS T/C: OR = 1.29, 95% CI = 0.95–1.75, P = 0.107). When stratified by ethnicity, the CTLA-4 -1722T/C polymorphism was associated with SLE only in Asians (T VS C: OR = 1.47, 95% CI = 1.10–1.96, P = 0.010; T/T VS C/C: OR = 2.09, 95% CI = 1.13–3.85, P = 0.018; T/C VS C/C: OR = 1.53, 95% CI = 0.87–2.69, P = 0.141; T/T VS T/C: OR = 1.42, 95% CI = 0.97–2.09, P = 0.070). In summary, the CTLA-4 -1722T/C polymorphism confers to SLE risk, especially in Asians.